The Analysis of Factors Affecting Original Local Government Revenue in Eastern Indonesia (Universitas Negeri Semarang, 2023)
The purpose of this study is to determine the effect of capital expenditure, investment, and Gross Regional Domestic Product (GRDP) of the primary sector, GRDP of secondary sector, and GRDP of tertiary sector on original local government revenue in Eastern Indonesia. This researchs is a quantitative research using secondary data. The research model is estimated using the Weighted Least Square (WLS) method to overcome the classical assumption problems that occur in the model. The results obtained from this study are: (1) Capital expenditure has an effect on original local government revenue, (2) Investment has no effect on original local government revenue, (3) GRDP of primary sector has an effect on original local government revenue, (4) GRDP of secondary sector has an effect on original local government revenue, (5) GRDP of tertiary sector has an effect on original local government revenue.